2020
DOI: 10.1093/bioinformatics/btaa1005
|View full text |Cite
|
Sign up to set email alerts
|

DeepPurpose: a deep learning library for drug–target interaction prediction

Abstract: Summary Accurate prediction of drug–target interactions (DTI) is crucial for drug discovery. Recently, deep learning (DL) models for show promising performance for DTI prediction. However, these models can be difficult to use for both computer scientists entering the biomedical field and bioinformaticians with limited DL experience. We present DeepPurpose, a comprehensive and easy-to-use DL library for DTI prediction. DeepPurpose supports training of customized DTI prediction models by implem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
239
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(239 citation statements)
references
References 15 publications
0
239
0
Order By: Relevance
“… Author Study keywords Targets No. of drugs Reference Ke, Y. Y Deep neural network FIP 80 Ke et al (2020) Ge, Y Knowledge Graph, deep learning SARS-CoV-2 64 Ge et al (2020) Beck, B. R Hybrid CNN and RNN model called MT-DTI 3CLpro, RdRp, helicase, 3′-to-5′ exonuclease, endoRNAse, and 2′-O-ribose methyltransferase 3410 Beck et al (2020) Zeng, X Deep learning-based knowledge graph (CoV-KGE), SARS-CoV-2 41 Zeng et al (2020) Gao, K 2-D fingerprint, GBDT model, Recurrent Neural Network (RNN) 3CLpro 40 Gao et al (2020) Hofmarcher, M Deep neural network, ChemAI 3CLpro, PLP 20 Hofmarcher et al (2020) Ton, A. T deep learning platform – Deep Docking (DD) Mpro 1000 Ton et al (2020) Hu, F Deep learning-based multi-task models, Classification and Regression 3CLpro 10 Hu and Jiang (2020) Gysi, D.M Graph Neural Network SARS-CoV-2 77 Gysi et al (2020) Huang, K Deep Purpose, Python toolkit, CNN 3CLpro 13 Huang et al (2020b) Batra, R Random forest (RF) regression algorithm, ensemble docking S, S-ACE2 complex 187 Batra et al (2020) Redka, D.S Deep learning, Ligand Design, MatchMaker, PolypharmDB 3CLpro, Spike; ACE2, TMPRSS2, Cathepsin B 30 Redka...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Author Study keywords Targets No. of drugs Reference Ke, Y. Y Deep neural network FIP 80 Ke et al (2020) Ge, Y Knowledge Graph, deep learning SARS-CoV-2 64 Ge et al (2020) Beck, B. R Hybrid CNN and RNN model called MT-DTI 3CLpro, RdRp, helicase, 3′-to-5′ exonuclease, endoRNAse, and 2′-O-ribose methyltransferase 3410 Beck et al (2020) Zeng, X Deep learning-based knowledge graph (CoV-KGE), SARS-CoV-2 41 Zeng et al (2020) Gao, K 2-D fingerprint, GBDT model, Recurrent Neural Network (RNN) 3CLpro 40 Gao et al (2020) Hofmarcher, M Deep neural network, ChemAI 3CLpro, PLP 20 Hofmarcher et al (2020) Ton, A. T deep learning platform – Deep Docking (DD) Mpro 1000 Ton et al (2020) Hu, F Deep learning-based multi-task models, Classification and Regression 3CLpro 10 Hu and Jiang (2020) Gysi, D.M Graph Neural Network SARS-CoV-2 77 Gysi et al (2020) Huang, K Deep Purpose, Python toolkit, CNN 3CLpro 13 Huang et al (2020b) Batra, R Random forest (RF) regression algorithm, ensemble docking S, S-ACE2 complex 187 Batra et al (2020) Redka, D.S Deep learning, Ligand Design, MatchMaker, PolypharmDB 3CLpro, Spike; ACE2, TMPRSS2, Cathepsin B 30 Redka...…”
Section: Resultsmentioning
confidence: 99%
“…They developed a multimodal approach that has combinations of different algorithms and further identified 77 potential repurposing drugs. Huang and colleagues ( Huang et al, 2020b ) developed a Python-based DL toolkit, DeepPurpose that is based on an encoder-decoder framework and presented a case study on SARS-CoV-2 3CL pro with 13 potential repurposing candidates identified. Batra et al (2020) trained and validated a random forest algorithm on data from Smith et al ( Smith and Smith, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, estimation of matrix of similarity limits the number of molecules. A DTI model which used DL, DeepDTA (K. Huang et al, 2021), was introduced to improve the above models. It used a CNN based model that waives requirements related to feature engineering.…”
Section: Drug Development Using ML For Covid-19mentioning
confidence: 99%
“…This model focuses on finding genes most relevant to the drug sensitivity prediction rather than the complete set of genes. DeepPurpose is another model that predicts IC 50 values [61]. Another critical property considered in drug designing is the compound's aqueous solubility.…”
Section: Prediction Of Drug-target Interactionsmentioning
confidence: 99%